Comparative Study of Nutritional Profile of Rice Varieties in Nepal - Pakuwal, Evance; Manandhar, Prakash (Nepal Journal of Biotechnology, 2021)
The purpose of this study was to evaluate and compare the nutritional quality of different rice varieties (Taichung-176, Khumal-4 rice, and Black rice) with Jumli Marsi rice. The highest nutritional factors and phytochemical components were found in the Marsi rice (RR) and Black rice (BR). The highest amount of antioxidant property and phenolic content was found in Black rice which was 61.58 ± 0.02% and 22.75 ± 0.02GAE/100g respectively. The reducing sugar was found to be highest in the TR rice variety, which was 2.74±0.01%. The results also highlight the cooking and physicochemical properties of rice depending on the amylose content of rice varieties. The qualitative analysis of the phytochemical content in different rice varieties showed the presence of tannin, flavonoid, alkaloid, and terpenoid in Marsi and BR. While anthraquinone and saponin were negative for all the rice varieties, protein and glycoside were found to be present in all the rice varieties. Also, the pigmented rice varieties were found to have high nutritional components compared to the non-pigmented rice varieties. All the data observed in the study was found to be statistically significant (p < 0.05).